Application of Artificial Intelligence in Determining the Learning Model of Islamic Religious Education (Pai)In Higher Education: Penerapan Artificial Inteligence Dalam Penentuan Model Pembelajaran Pendidikan Agama Islam (Pai) Di Perguruan Tinggi - Efriyanti, Liza (Procedia of Social Sciences and Humanities, 2024)
The role of Islamic education in higher education institutions is pivotal in shaping students' character, morals, and religious understanding. However, the diversity in students' cultural backgrounds, levels of comprehension, and learning styles presents challenges in designing effective and personalized learning strategies. Success in Islamic education at the tertiary level hinges not only on the content of the material but also on the methodologies employed to convey religious values and foster deep understanding.In the era of technological advancement and the Information Society 5.0, traditional approaches to Islamic education may need to be adapted to more adaptive and personalized methods. Each student has unique learning preferences, varying levels of comprehension, and individual challenges in relating religious teachings to everyday life. Thus, innovative approaches are necessary to determine optimal learning strategies.Fuzzy logic, a component of artificial intelligence, can address the complexities in decision-making.Fuzzy logic allows for more flexible measurement by enabling values between 0 and 1, reflecting the degree of membership of an element in a particular set. The application of fuzzy logic is expected to make decision-making regarding Islamic education strategies more adaptive, accurate, and tailored to individual characteristics.